Efficient Sulfate Adsorption on Modified Adsorbents Prepared from Zea mays Stems - Candelaria Tejada-Tovar; Ángel Villabona-Ortíz; Angel Dario Gonzalez-Delgado; Adriana Herrera; Andrea Viera De la Voz (Applied Sciences, 2021)
The effect of temperature on the sulfate adsorption capacity of adsorbents prepared from corn stalks (Zea mays) was evaluated. Two bioadsorbents were prepared from biomass: a biochar modified with H2SO4 with mass: volume ratio 1:1 (B 1:1), and cellulose modified with cetyl trimethyl ammonium chloride (CTAC). There were also determined thermodynamic parameters (ΔG°, ΔS° and ΔH°) and it was studied the adsorption kinetics and isotherm. At 25 °C was obtained the highest adsorption capacity of 16.4 and 7.4 mg/g with mass/volume ratio B 1:1 and modified corn (MC) respectively; it was observed an adverse effect of temperature increase on bioadsorbents’ performance. The thermodynamic parameters showed that the adsorption process is exothermic, not spontaneous, and it was given by chemisorption. Adsorption kinetics showed that equilibrium was reached at 420 min and that the pseudo-second-order model adjusted the experimental data with R2 > 0.98 and qe of 16.64 and 7.48 mg/g for B 1:1 as well as MC. The adsorption isotherm showed a good fit to Freundlich’s model when using B 1:1, whereas using MC as adsorbents the data was adjusted by Dubinin-Radushkevich’s model. Zea mays stems are an abundant agricultural residue and are a good source for the preparation of biochar type bioadsorbents as well as the extraction of cellulose, its use is recommended in the removal of sulfates in solution.